Evidence of large increases in sedimentation rates due to fish trawling in submarine canyons of the Gulf of Palermo (SW Mediterranean). (November 2021) - Paradis, Sarah; Lo Iacono, Claudio; Masqué, Pere; Puig, Pere; Palanques, Albert; Russo, Tommaso
Abstract: Bottom trawling in submarine canyons can affect their natural sedimentation rates, but studies addressing this issue are still scarce. In the Gulf of Palermo (SW Mediterranean), bottom trawling occurs on the slope around Oreto, Arenella and Eleuterio canyons. Analyses of excess 210 Pb concentrations and grain size fractions in sediment cores from their canyon axes revealed that sedimentation rates and silt contents increased in all canyons in the 1980s, due to the expansion of more powerful trawlers (>500 HP) to deeper fishing grounds. In Eleuterio and Arenella canyons, sedimentation rates increased by an order of magnitude (0.1-1.4 cm·yr -1 ), whereas they increased less (0.1-0.7 cm·yr -1 ) in Oreto Canyon, since the enhanced trawling-derived sediment fluxes into this canyon are affected by sediment resuspension from trawling along its axis. Considering the global expansion of bottom trawling, we anticipate similar alterations in other trawled canyons, with ecological consequences that should be addressed by management strategies. Highlights: Sedimentation rates increased in Palermo submarine canyons in the 1980s. Sedimentation rates increased by an order of magnitude in some canyons. Increased sedimentation rates were associated to resuspension by bottom trawling. The change in sedimentation occurred after the trawling fleet industrialization.